New Age communities in the Central Plateau: utopia, ideology and reafirmation of order - Nogueira, Aico Sipriano (Tempo Social, 2001)
This article analyses the constitution of an alternative community in the central plateau of Brazil, based on what has been called 'new contemporary forms of sociability'.Using a theoretical-conceptual discussion on community, utopian community, myth, ideology, utopia and imaginary, the text suggests the possibility of taking the idea of alternative to the present social system as an expression, along with conservative thought and the possibility of the construction of the new.